Mali’s first-ever Community-Based Breeding Program is launched - Tebourbi, Ons; Getachew, Tesfaye; Dione, Michel; sow, ahmadou; Rekik, Mourad; Marshall, Karen; Haile, Aynalem; Rischkowsky, Barbara; Sacko, Idrissa; Dao, Madou; Doubangolo, Coulibaly (International Center for Agricultural Research in the Dry Areas, 2025)
The launch in Mali in 2023 of the country’s first-ever community-based breeding scheme for goats demonstrates that when small-scale livestock keepers collaborate, they can improve the genetic potential of their goats and enhance their livelihoods.